Pemanfaatan Kulit Ari Kedelai sebagai Bahan Pembuatan Nugget untuk Peningkatan Gizi Anak Stunting: Soybean Husk as the Nugget Basic Ingredient to Improve the Nutrition of Stunting - Sinta Ratna Dewi; Rizki Nur Azmi; Ika Ayu Mentari; Vera Herliani Pratiwi; Erlinda Dwi Afriliani; Nabilah Husna Fitriyani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Reducing the incidence of stunting in Indonesia is a top priority in overcoming health problems. Mesjid Ward, Samarinda City, is one of the areas that has a high prevalence of stunting, with as many as 34 children in 2020. Efforts to overcome this problem need to use unconventional food ingredients that contain adequate nutrition, are affordable, and are easy to obtain. Soybean husk, which has a high protein and fiber content, has the potential to be utilized in efforts to fulfill stunting children's nutrition. Community service activities aim to increase the utilization of soybean husk as processed healthy nuggets, increase public knowledge regarding stunting, and improve community skills in processing soybean husk-based nuggets—activities carried out by providing counseling and training. The results of this activity indicated that there was a significant change in the community's knowledge after giving the material (p-value <0.001). The knowledge about stunting and how to use soybean husk in processed food products has increased among the public.